Hubungan antara Kemampuan Spasial dengan Prestasi Belajar Matematika - Tambunan, Siti Marliah (Makara Human Behavior Studies in Asia, 2006)
A number of the mathematical problem solving are related with visuospatial ability. A good spatial conceptualization is an asset to understand the mathematical concept. Perspective understanding, geometrical shapes, and visual concept relation are crucial skills in spatial ability. These factors are also needed in mathematical performance. This research is intended to test the relationship between spatial abilities and mathematical performance. Data are collected from 220 children (7 to 11 years old) by giving them the spatial ability test which consists of spatial topology, projective, euclidis, and mathematical test. Result shows that there is a significant relationship between total spatial ability, topology, euclidis and mathematical performance. In the contrary, it shows that there is no relationship between projective spatial ability and mathematical performance.